Effects of perceived autonomy support from social agents on motivation and engagement of Chinese primary school students: Psychological need satisfaction as mediator - Zhou, L.H.; Ntoumanis, Nikos; Thogersen-Ntoumani, Cecilie (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
© 2019 Elsevier Inc. Little research has simultaneously examined the differential effects of autonomy support from parents, teachers, and peers (social agents) on students’ psychological need satisfaction, motivation, and school engagement. Drawing from Self-Determination Theory, this study examined the joint effects of perceived autonomy support from these three social agents on psychological needs, motivation, and engagement of 614 Chinese primary school students. Results revealed that perceived autonomy support from parents, teachers, and peers positively and uniquely predicted student psychological need satisfaction. The effect was strongest for parental autonomy support, although a model constraining the paths from all three social agents to be equal fit equally well. Need satisfaction predicted greater self-determined motivation and student engagement and mediated the effects of all three social agents on student motivation and engagement. The model showed strong gender invariance. The results highlight the importance of targeting all three social agents in multi-level interventions that aim to optimize student motivation and school engagement.